Fiscal Discretion and Its Impact on Pakistan Economy (The Pakistan Development Review, 2012)
Macroeconomics addresses output, employment and price fluctuations during business cycles. Business cycles which capture variation in economic activity emerge generally due to instable investment, frequent changes in money and credit through banking system and unmanageable haphazard proceedings of wars or political instability. Business cycles inherent features of mixed economic system where households and businesses composed of different motivations spend and produce, differ in their respective economic activities. The occurrence of this difference results in creation of waves in economic activities, which are the business cycles [Spencer and Amos (1993)]. Output variation in moderate context is either a recession or recovery. During recession the economic activity falls which not only reduces employment opportunities but creates gap between potential and actual output of an economy. The federal government tries to keep the adverse effects of business cycle at bay all together. Economists admit that private sector is unable to protect the economy from uncontrolled variations in employment and inflation. In this scenario the government’s fiscal management is corrective response for the problems of recovery and recession. The government makes use of public spending and taxes to minimise the gap of business cycles. This process is called fiscal policy and the deliberate government involvement to stabilise economy is regarded as discretionary fiscal policy. The government can make use either taxes or government spending or both to stabilise economy but in this study we only used government spending due to its larger and positive multiplier effects.